Coating of Carbon Nanotube Fibers: Variation of Tensile Properties, Failure Behavior, and Adhesion Strength - Mäder, Edith; Liu, Jianwen; Hiller, Janett; Lu, Weibang; Li, Qingwen; Zhandarov, Serge; Chou, Tsu-Wei (Frontiers in Materials, 2015)
An experimental study of the tensile properties of CNT fibers and their interphasial behavior in epoxy matrices is reported. One of the most promising applications of CNT fibers is their use as reinforcement in multifunctional composites. For this purpose, an increase of the tensile strength of the CNT fibers in unidirectional composites as well as strong interfacial adhesion strength is desirable. However, the mechanical performance of the CNT fiber composites manufactured so far is comparable to that of commercial fiber composites. The interfacial properties of CNT fiber/polymer composites have rarely been investigated and provided CNT fiber/epoxy interfacial shear strength of 14.4 MPa studied by the microbond test. In order to improve the mechanical performance of the CNT fibers, an epoxy compatible coating with nano-dispersed aqueous based polymeric film formers and low viscous epoxy resin, respectively, was applied. For impregnation of high homogeneity, low molecular weight epoxy film formers and polyurethane film formers were used. The aqueous based epoxy film formers were not crosslinked and able to interdiffuse with the matrix resin after impregnation. Due to good wetting of the individual CNT fibers by the film formers, the degree of activation of the fibers was improved leading to increased tensile strength and Young’s modulus. Cyclic tensile loading and simultaneous determination of electric resistance enabled to characterize the fiber’s durability in terms of elastic recovery and hysteresis. The pull-out tests and SEM study reveal different interfacial failure mechanisms in CNT fiber/epoxy systems for untreated and film former treated fibers, on the one hand, and epoxy resin treated ones, on the other hand. The epoxy resin penetrated between the CNT bundles in the reference or film former coated fiber, forming a relatively thick CNT/epoxy composite layer and thus shifting the fracture zone within the fiber. In contrast to this, shear sliding along the